Arabinogalactan Proteins Are Involved in Salt-Adaptation and Vesicle Trafficking in Tobacco by-2 Cell Cultures - Olmos, Enrique; García De La Garma, Jesús; Gomez-Jimenez, Maria C.; Fernandez-Garcia, Nieves (Frontiers in Plant Science, 2017)
Arabinogalactan proteins (AGPs) are a highly diverse family of glycoproteins that are commonly found in most plant species. However, little is known about the physiological and molecular mechanisms of their function. AGPs are involved in different biological processes such as cell differentiation, cell expansion, tissue development and somatic embryogenesis. AGPs are also involved in abiotic stress response such as salinity modulating cell wall expansion. In this study, we describe how salt-adaptation in tobacco BY-2 cell cultures induces important changes in arabinogalactan proteins distribution and contents. Using the immuno-dot blot technique with different anti-AGP antibodies (JIM13, JIM15 and others), we observed that AGPs were highly accumulated in the culture medium of salt-adapted tobacco cells, probably due to the action of phospholipases. We located these AGP epitopes using immunogold labelling in the cytoplasm associated to the endoplasmic reticulum, the golgi apparatus and vesicles, plasma membrane and tonoplast. Our results show that salt-adaptation induced a significant reduction of the cytoplasm, plasma membrane and tonoplast content of these epitopes. Yariv reagent was added to the control and salt-adapted tobacco cell cultures, leading to cell death induction in control cells but not in salt-adapted cells. Ultrastructural and immunogold labelling revealed that cell death induced by Yariv reagent in control cells was due to the interaction of Yariv reagent with the AGPs linked to the plasma membranes. Finally, we propose a new function of AGPs as a possible sodium carrier through the mechanism of vesicle trafficking from the apoplast to the vacuoles in salt-adapted tobacco BY-2 cells. This mechanism may contribute to sodium homeostasis during salt-adaptation to high saline concentrations.